An energy-aware resource design model for constrained networks - Correia, N. (2017)
The Internet of Things is expected to incorporate objects and sensor networks of all kinds, and in particular, constrained sensor networks where energy consumption is a critical issue. In order to increase the lifetime of such networks, intelligent and standard-based solutions should be used. Here, we address this challenge through the use of CoRE interfaces for the resource design. These interfaces allow the server side to compose/organize resources and the client side to discover and determine how to consume such resources, besides allowing decisions to be easily integrated into the operation of the network. An energy-aware resource design model is proposed, based on CoRE interfaces, for the design of resources matching client needs. Based on this model, we develop an algorithm that proved to be energy efficient.